THE INFLUENCE OF PRODUCT QUALITY, PRICE PERCEPTION, AND CUSTOMER VALUE ON CONSUMER SATISFACTION OF ROLL PRODUCTS IN SIDOARJO THROUGH SOCIAL MEDIA - Dewa Ananda Medy Pratama; Endah Budiarti (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This research uses quantitative research which was conducted to determine the variables of product quality, price perception and customer value on consumer satisfaction of roll products in Sidoarjo via social media. This research aims to analyze the influence of product quality, price perception and customer value on consumer satisfaction of roll products in Sidoarjo via social media. This research uses primary data obtained from 85 respondents who have purchased roll products. To test the variables, researchers used statistical tools, namely: Structural Equation Modeling (SEM) Partial Least Squares (PLS). The results of this research stated that it has a significant relationship with product quality, price perception and customer value on customer satisfaction with Roll products.